A Critical Review of History of Culture and Art of Iran (Before the Islam) - Javad HoseinzadehSadati (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The culture and arts of ancient Iran is so rich that after a century, the researchers are still introducing them and yet they remained flourishing. The book of “History of Culture and Art of Iran (Before the Islam)” is one of the text that is prepared to introduce pre-Islamic culture and art of Iran to interested students and people. From diachronic point of view, this book has tried to introduce  different aspects of Pre-Islamic culture and arts of Iran briefly to the next generation. Today one the biggest problems all around the world, which includes us, is the crisis of identity, and such texts that introduce our ancient cultures to the new generations of students is necessary. This paper first reviews the format and content of the book, and then it proposes some points that can improve the next publications if the authors apply them.